O caso dos irmãos Naves: processamentos artísticos a partir de um erro jurídico - Oliveira, Eliene Rodrigues de (2013)
The book O Caso dos Irmãos Naves (1960), wrote by João Alamy Filho and grounded in the records of the lawsuit of the Araguari\'s classical judicial error (1937-1953), was adapted into an homonymous film directed by Luiz Sérgio Person in 1967. Both book and film turned to be a celebration in memoriam of Naves family and opened a branch full of possibilities in kindling to the general public (and in other artists) the consciousness of individual and social responsibility. Besides, there are many songs, television shows and plays based on both Alamy Filho\'s book and Person\'s film. This paper aims a study of the artistic processing of the Naves brothers\' suffering regarding to memory devices and revealing that art is important in sustaining and rewriting the social memory.